Development of multi‐disciplinary breast cancer care in Southern Malawi. (January 2017) - Brown, E.R.S.; Bartlett, J.; Chalulu, K.; Gadama, L.; Gorman, D.; Hayward, L.; Jere, Y.; Mpinganjira, M.; Noah, P.; Raphael, M.; Taylor, F.; Masamba, L.
Abstract : The Edinburgh Malawi Breast Cancer Project, a collaborative partnership project between the Queen Elizabeth Central Hospital (QECH) Oncology Unit, Blantyre, Malawi and the Edinburgh Cancer Centre, UK, was established in 2015. The principal objective of the project is to help to develop high quality multi‐disciplinary breast cancer care in Malawi. A needs assessment identified three priority areas for further improvement of breast cancer services: multi‐disciplinary working, development of oestrogen receptor (ER) testing and management of clinical data. A 3‐year project plan was implemented which has been conducted through a series of reciprocal training visits. Key achievements to date have been: (1) Development of a new specialist breast care nursing role; (2) Development of multi‐disciplinary meetings; (3) Completion of a programme of oncology nursing education; (4) Development of a clinical database that enables prospective collection of data of all new patients with breast cancer; (5) Training of local staff in molecular and conventional approaches to ER testing. The Edinburgh Malawi Breast Cancer Project is supporting nursing education, data use and cross‐specialty collaboration that we are confident will improve cancer care in Malawi. Future work will include the development of a breast cancer diagnostic clinic and a breast cancer registry.